Analisis Most Probable Number (MPN) Bakteri Coliform pada Sampel Air Minum sebagai Upaya Pemantauan Kualitas Air: Indonesia - Akidah, Nur Akidah Tahir; Ramadhani, Zahwa; Asrianti, Andi Melisa; Masri, Mashuri (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
This study aims to analyze Coliform bacteria in drinking water samples using the Most Probable Number (MPN) method. Water samples were obtained from three different drinking water depots in Bone Regency. Testing was carried out in three stages, namely presumptive test, confirmed test, and completed test with Lactose Broth (LB) and Brilliant Green Lactose Broth (BGLB) media. The test results showed that sample A had the highest MPN index of 27 per 100 mL, followed by sample C at 20 per 100 mL, and sample B at 16 per 100 mL. These values exceeded the maximum limit set by Indonesian Minister of Health Regulation No. 492 of 2010, which means that all samples did not meet the requirements for potable water. The results serve as a reminder of humanity's responsibility as caliphs to preserve the purity of water as a blessing from Allah. Allah's words in QS. Ar-Rum/30:41 affirms that damage to land and sea occurs because of human actions. Therefore, maintaining the cleanliness of water sources is a form of ecological worship that reflects balance (tawazun) and trustworthiness towards nature.